Polyethylene oxide and its controlled release properties in hydrophilic matrix tablets for oral administration. (25th November 2020) - Vanza, Jigar D.; Patel, Rashmin B.; Dave, Richa R.; Patel, Mrunali R.
Abstract: Polymers are excipients that modify the rate of drug release from pharmaceutical dosage forms. Hydrophilic polymer-based controlled drug delivery system is more advantageous as compared to the conventional delivery system as it reduces the dosing frequency, improves therapeutic efficacy, reduces side-effects, and probably enhances patient compliance. Polyethylene oxide (PEO), a nonionic hydrophilic polymer, is one of the most widely used polymers for extending the drug release. This review mainly focuses on the PEO marketed by, but not limited to, The Dow Chemical Company under the trade name of POLYOX TM . It is commercially available polyethylene oxide polymer existing in various molecular weight and viscosity grades depending upon the application. This study essentially discusses chemistry, physicochemical properties, and the impact of formulation and processing variables on the release of drug from hydrophilic PEO matrix tablets. Moreover, it also summarizes the stability, patents, and regulatory perspectives of POLYOX that can further influence the future developments of controlled release dosage forms.